RGB-based colorimetric method for the analysis of water alkalinity using Cordyline fruticosa extracts as visual indicator - Parungao, Christian Alex C.; Reyes, Darwin F. (International Journal of Public Health Science (IJPHS), 2024)
Leaf extracts of Cordyline fruticosa was used as a natural visual indicator for a digital image-based analytical procedure for the measurement of water alkalinity. A smartphone and ImageJ were used to capture and process the images, respectively. This work sought to develop and evaluate a greener strategy of using of Cordyline fruticosa leaf extract as natural indicator, in a digital image-based colorimetric set-up using smartphone. Under optimized conditions, the linear working range was from 40 to 160 ppm of CaCO3, with a calibration sensitivity of 5 x 10-3 ppm and a coefficient of correlation (r2)=0.998. The limit of detection and quantification were 39 ppm and 117 ppm, respectively. A 10,000 ppm CaCO3 solution was tested using the proposed method and the results statistically agree with the results obtained from titrimetric methods. The study presented a simple analytical procedure that can be develop and apply for the assessment of pollution that could pose serious human and environmental health hazards.